Regenerative Medicine in South Korea: Bridging the Gap Between Authorization and Reimbursement - Kim, Dong-Sook; Lee, Geunwoo; Cho, Hyungyung; Bae, SeungJin (Frontiers in Bioengineering and Biotechnology, 2021)
Regenerative medicine (RM) has considerable potential to address the needs of aging-related and uncurable diseases. However, its incorporation into reimbursement of health insurance benefits poses many challenges, including uncertain evidence and insufficient investment. This paper examines the wide gap between manufacturers, regulatory bodies, and health technology bodies regarding reimbursements for RMs focused cell therapy products. In this mixed-methods study, we first analyzed the sales of RMs approved in South Korea. In addition to exploring beliefs related to the market value of RMs, in-depth interviews were conducted with 24 experts (17 from bio-industries, 2 from the regulatory body, 3 from a health technology assessment (HTA) body, and 2 from the Pharmaceutical Benefit Coverage Assessment Committee [PBCAC]). Lastly, we surveyed PBCAC members about the market value of RMs. In total, 15 of the 20 developed RMs are on the market in South Korea, and amounted to 0.24% of total pharmaceutical expenditures in 2018. We identified a wide gap between stakeholders and regulators regarding the market value and pricing of RMs. The interviewees from the pharmaceutical manufacturer association raised the issue of rising manufacturing costs and proposed a specific pricing policy for RMs. To bridge the gap between approval and reimbursement, stakeholders demand an alternative framework of value-based pricing. Conditional health insurance reimbursement may be an alternative to the traditional process in order to generate evidence of the effects of RMs using “risk-based” or “outcome-based” approaches.